Association between vitamin D receptor gene haplotypes and chronic periodontitis among Japanese men - Mariko Naito, Koichi Miyaki, Toru Naito, Ling Zhang, Keika Hoshi, Asako Hara, Katsunori Masaki, Shugo Tohyama, Masaaki Muramatsu, Nobuyuki Hamajima, Takeo Nakayama (International Journal of Medical Sciences, 2007)
Background: The vitamin D receptor (VDR) is involved in a variety of biological processes, such as bone metabolism and modulation of the immune response. Recent findings suggest that the pathway involving bone mineral density-mediated effects is important for the development of periodontitis, but their effects of combined VDR gene polymorphisms have not been confirmed on periodontitis. We assessed the relationship between ApaI, BsmI, and FokI VDR polymorphisms and the risk of severe chronic periodontitis among Japanese adult men. Materials and Methods: In a cross-sectional study, we examined 97 unrelated healthy Japanese men (mean age: 45.6 years, range: 22-59). A clinical examination was performed at a worksite health checkup, and information was obtained using a self-reported questionnaire. DNA was extracted from whole blood, and the VDR ApaI, BsmI, and FokI polymorphisms were genotyped using polymerase chain reaction. Results: F-carriers of FokI VDR polymorphisms were less likely to develop severe chronic periodontitis than non-F-carriers (p = 0.09). The ApaI and BsmI VDR polymorphisms did not show significant differences in the alleles or genotypes between the subjects with or without severe chronic periodontitis. The haplotype analysis of the three combined VDR polymorphisms revealed that the Abf homozygote had a notably higher prevalence of severe chronic periodontitis than the others, and adjustments for age, smoking status, number of teeth present, and prevalence of diabetes did not change this association (OR = 7.5; 95% CI = 1.6-34.4; p = 0.01). Conclusion: The VDR haplotype constructed from the ApaI, BsmI, and FokI polymorphisms is related to the risk of severe chronic periodontitis in Japanese men.